Perceived accountability and public attitudes toward local police. Issue 3 (2nd July 2016) - De Angelis, Joseph; Wolf, Brian
Abstract: Recent national events have brought the issue of police-community relations into the public eye. Even though a large body of academic research exists on the predictors of public attitude toward police, very little is known about how public perceptions of police accountability influence satisfaction with the police. This study seeks to fill that gap by using ordered logistic regression and multi-year community-level survey data from one Western city ( n = 3725) to examine the relationship between satisfaction with police accountability and overall attitudes toward the police. The results indicate that respondent satisfaction with police accountability was a strong, consistent predictor of satisfaction with local police, even after controlling for other important variables, such as race/ethnicity and community context. The findings suggest that public perceptions relating to the control of police officer conduct should be considered when assessing the predictors of attitudes toward the police.